Patient‐specific Virtual Temporal Bone Simulation Based on Clinical Cone‐beam Computed Tomography. (29th March 2021) - Andersen, Steven Arild Wuyts; Varadarajan, Varun V.; Moberly, Aaron C.; Hittle, Bradley; Powell, Kimerly A.; Wiet, Gregory J.
Abstract : Objectives: Patient‐specific surgical simulation allows presurgical planning through three‐dimensional (3D) visualization and virtual rehearsal. Virtual reality simulation for otologic surgery can be based on high‐resolution cone‐beam computed tomography (CBCT). This study aimed to evaluate clinicians' experience with patient‐specific simulation of mastoid surgery. Methods: Prospective, multi‐institutional study. Preoperative temporal bone CBCT scans of patients undergoing cochlear implantation (CI) were retrospectively obtained. Automated processing and segmentation routines were used. Otologic surgeons performed a complete mastoidectomy with facial recess approach on the patient‐specific virtual cases in the institution's temporal bone simulator. Participants completed surveys regarding the perceived accuracy and utility of the simulation. Results: Twenty‐two clinical CBCTs were obtained. Four attending otologic surgeons and 5 otolaryngology trainees enrolled in the study. The mean number of simulations completed by each participant was 16.5 (range 3–22). "Overall experience" and "usefulness for presurgical planning" were rated as "good, " "very good, " or "excellent" in 84.6% and 71.6% of the simulations, respectively. In 10.7% of simulations, the surgeon reported to have gained a significantly greater understanding of the patient's anatomy compared to standard imaging. Participants were able to better appreciate subtle anatomic findings after using the simulator for 60.4% of cases. Variable CBCT acquisition quality was the most reported limitation. Conclusion: Patient‐specific simulation using preoperative CBCT is feasible and may provide valuable insights prior to otologic surgery. Establishing a CBCT acquisition protocol that allows for consistent segmentation will be essential for reliable surgical simulation. Level of Evidence: 3 Laryngoscope, 131:1855–1862, 2021